2008
DOI: 10.1002/job.529
|View full text |Cite
|
Sign up to set email alerts
|

To prosper, organizational psychology should … overcome methodological barriers to progress

Abstract: SummaryProgress in organizational psychology (OP) research depends on the rigor and quality of the methods we use. This paper identifies ten methodological barriers to progress and offers suggestions for overcoming the barriers, in part or whole. The barriers address how we derive hypotheses from theories, the nature and scope of the questions we pursue in our studies, the ways we address causality, the manner in which we draw samples and measure constructs, and how we conduct statistical tests and draw infere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
132
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(141 citation statements)
references
References 167 publications
(200 reference statements)
3
132
1
5
Order By: Relevance
“…So, the true associations might be weaker than the relationships observed in this study. Although several studies have shown that these influences are not as high as could be expected [61][62][63] , our findings should be replicated with objective measures (e.g., actual time at work as an index of job demands) in the future. However, a special feature of our study is that instead of measuring only self-reported WFC, we asked participants to provide information about the WFC of their partner as well.…”
Section: Study Limitations and Strengthsmentioning
confidence: 45%
“…So, the true associations might be weaker than the relationships observed in this study. Although several studies have shown that these influences are not as high as could be expected [61][62][63] , our findings should be replicated with objective measures (e.g., actual time at work as an index of job demands) in the future. However, a special feature of our study is that instead of measuring only self-reported WFC, we asked participants to provide information about the WFC of their partner as well.…”
Section: Study Limitations and Strengthsmentioning
confidence: 45%
“…The first concerns reverse causality-the possibility that performance drives the usage of image-based words rather than, as we theorize, the other way around. We conducted tests recommended by Edwards (2008).…”
Section: Endogeneity Checksmentioning
confidence: 99%
“…Indirect measures are based on the spontaneous reactions of the subjects, which are diffi cult to control and "reveal not fully conscious affect or motives or respondents" (Böhner & Wänke, 2002;Edwards, 2008;Greenwald & Banaji, 2005). The most popular method of indirect measurement in organizational research is the Implicit Association Test (Greenwald & Farnham, 2000;Greenwald, McGhee, & Schwartz, 1998) based on the measurement of reaction time in categorization tasks.…”
Section: New Indirect Measure Of Attitude Towards Occupationmentioning
confidence: 99%